Dampak Pandemi terhadap Pembelajaran di Era Pandemic Covid-19 - Cisia Padila (PAKAR Pendidikan, 2020)
As a result of the pandemic that started in Wuhan, China and spread to all corners of the world including Indonesia. Impact felt by residents the world including Indonesia is very complicated. The number of employees who have been laid off has led to a decline in the economy which has affected the education sector. Physical distancing that is applied has many impacts on people's lives. Markets, malls, offices and even schools are closed. All activities are carried out online, even for schools, which are usually face-to-face, are now held virtually. The number of complaints that arise because of this pandemic starts from complaints about assignments because teachers only give assignments without explaining first, on the other hand students are told to learn and maintain health. We know that the large number of tasks given by the teacher indirectly affects the mental health of students. Another problem is the single tuition fee (UKT) which sometimes gets stuck because parents are laid off creates new problems and often this makes students drop out of school / college. In this case the role of government is needed. The government is expected to go directly to the field to review the conditions of the affected communities. Not only entrusting it to subordinates or officials. Especially in the field of education because the education of the nation's children is the main hope of the Indonesian nation. This research uses the literary method and it is hoped that this research can have an influence on education in Indonesia and education can get great attention by the government.